Modern Japan's Place in World History From Meiji to Reiwa - Yamauchi, Masayuki; Hosoya, Yuichi (Springer Nature Singapore : Imprint: Springer, 2023)
This Open Access book includes chapters on the key turning points in modern Japanese history from the Meiji Restoration to Japan-China diplomatic normalization in the 1970s and beyond. The topics covered include the First Sino-Japanese War, the Russo-Japanese War, the First and Second World Wars, the Manchurian Crisis, the US Occupation, postwar Japan-China relations, and postwar decolonization. Readers will learn how new research by Japanese historians has led to the revision of conventional views on the turbulent history of Japan, once the enemy of the United States in the war in the Asia-Pacific and now the US's closest ally in the region. Historical research on the modern history of Japan has been constantly updated. From the Meiji Restoration to the present day, Japan has experienced the effects of modernization and globalization. Recent historical inquiries in Japan tend to focus on the merging of modern history with global history. During the past 150 years, Japan has never been separated from events in international affairs. Scholars and general readers will appreciate the new factual details and philosophical perspectives that this volume provides drawing on the work of fourteen authors who are recognized leaders in their fields. Yuichi Hosoya is Professor of International Politics at Keio University. Masayuki Yamauchi is Specially Appointed Professor at the Musashino University Institute for Global Affairs and Professor Emeritus, the University of Tokyo.